Steady-state assessments of PMSGs in wind generating units. (September 2017) - Bonfiglio, A.; Delfino, F.; Gonzalez-Longatt, F.; Procopio, R.
Highlights: We proposed an analytical approach to evaluate the steady state capabilities of PMSG in wind generating units. Methodology aimed at supporting the proper design of the PMSG. Methodology applicable for various control strategies of the machine side converter. Abstract: The number of fully-rated converter wind turbine generators equipped with a Permanent Magnet Synchronous Generator (PMSG) has sensibly increased in the late years. The optimal utilization and controllability of a PMSG is achieved using a Pulse Width Modulation – Voltage Source Converter (PWM-VSC) that allows interfacing the electric machine with the distribution network by means of a DC link. The generator/Machine-Side Converter (MSC) controls the operation of the PMSG. This paper proposes a methodology to assess the feasibility of the steady-state working points of PMSG based wind turbines without running a set of time-consuming time-domain simulations. Three control objectives for MSC are usually considered: stator voltage control, unitary power factor control and torque control. The aim of the present paper is that of providing an analytical methodology to check the feasibility of the steady-state working points dictated by different control strategies of the MSC starting from the specific operational constraints provided by the wind power plants characteristics. The effectiveness of the proposed methodology is demonstrated comparing numerical results of a MATLAB® implementation against dedicated time-domain simulations. Simulations results demonstrated the appropriate performance of the proposed methodology characterized by the almost negligible computational time required.